Adiponectin and Endothelin-1 are Correlated with the Development of Normal-tension Glaucoma in Metabolic Syndrome Patients - Prayitnaningsih, Seskoati; Oktarina, Virna Dwi; Nusanti, Syntia; Diarsvitri, Wienta; Rif'ati, Lutfah; Siswanto, Bambang Budi; Santoso, Anwar (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Glaucoma can lead to irreversible blindness, but normotension glaucoma (NTG) often shows no early symptoms. However, to date, there is limited knowledge regarding the potential parameters for early detection. Therefore, in this study, various metabolic parameters and biomarkers which may contribute to NTG in metabolic syndrome (MetS) patients were evaluated.METHODS: A retrospective cross-sectional study was conducted in the National Cardiac Center Harapan Kita Hospital. Mets were confirmed following the IDF criteria. NTG was determined based on normal intraocular pressure (IOP) with a mean defect (MD) of the visual field, thinning of the retinal nerve fiber layer (RNFL), and enlargement of cup disc ratio (CDR) by ocular coherence tomography (OCT). Metabolic parameters results of waist circumference (WC), body weight, body height, body mass index (BMI), blood pressures, HbA1c, fasting blood glucose (FBG), lipid profiles; and biomarkers including thiobarbituric acid reactive substance (TBARS) and ferric reducing antioxidant power (FRAP), leptin, adiponectin, high-sensitivity C-reactive protein (hs-CRP), and endothelin-1 (ET-1) were analyzed. Statistical analysis was performed using comparative and correlative tests.RESULTS: From 29 subjects, 19 subjects (65.5%) were included in the NTG group and 10 subjects (34.5%) were included in the non-NTG group. In the NTG group, we found significant correlation between MD with systolic blood pressure (p=0.035); CDR with ET-1 (p=0.049); and CDR with adiponectin (p=0.010). The non-NTG group had a significant correlation between MD with BMI (p=0.043); CDR with LDL (p=0.042); and CDR with TG (p=0.031).CONCLUSION: There are correlation between adiponectin and ET-1 with NTG in MetS patients. Therefore, they might be considered as potential early detectors for NTG in MetS patients.KEYWORDS: normal tension glaucoma, metabolic syndrome, biomarker, endothelin-1, adiponectin